2006
DOI: 10.1134/s0006297906090082
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin activates cytochrome c peroxidase activity since it facilitates H2O2 access to heme

Abstract: In this work, the effect of liposomes consisting of tetraoleyl cardiolipin and dioleyl phosphatidylcholine (1 : 1, mol/mol) on the rate of three more reactions of Cyt c heme with H2O2 was studied: (i) Cyt c (Fe2+) oxidation to Cyt c (Fe3+), (ii) Fe...S(Met80) bond breaking, and (iii) heme porphyrin ring decomposition. It was revealed that the rates of all those reactions increased greatly in the presence of liposomes containing cardiolipin and not of those consisting of only phosphatidylcholine, and approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 42 publications
0
34
0
2
Order By: Relevance
“…A peculiar event that accompanies the energy collapse is the intra-mitochondrial degradation of cyt c, a protein not only involved in respiration (Vladimirov et al 2006). We reported that ROS produced in GL15 cells after bromopyruvate or menadione treatment could be responsible for the intra-mitochondrial cyt c degradation (Macchioni et al 2011a).…”
Section: Discussionmentioning
confidence: 97%
“…A peculiar event that accompanies the energy collapse is the intra-mitochondrial degradation of cyt c, a protein not only involved in respiration (Vladimirov et al 2006). We reported that ROS produced in GL15 cells after bromopyruvate or menadione treatment could be responsible for the intra-mitochondrial cyt c degradation (Macchioni et al 2011a).…”
Section: Discussionmentioning
confidence: 97%
“…93 The iron coordination in the heme of cytochrome c is disrupted 94 allowing H 2 O 2 generated from other sites, perhaps the ETC itself, to interact with the heme iron of cytochrome c and peroxide CL. 94 In vitro, cytochrome c-CL interactions generate monoepoxides of linoleic acid as an oxidation product of the CL. 95 CL peroxidase activity has been described in isolated mitochondria and the peroxidation of CL shown in intact cells as a key contributor in the cascade of reactions leading to programmed cell death.…”
Section: Oxidative Damagementioning
confidence: 99%
“…Depending on the experimental conditions, the sixth coordination position of the heme iron remains unbound or is occupied by another side chain (likely a Lys or a His residue) [7,20,21]. The partially unfolded conformation of membranebound cyt c induces a drastic change of the redox potential and favors its peroxidase activity [22], facilitating the access of small molecules (such as hydrogen peroxide) into the heme pocket region [23].…”
Section: Introductionmentioning
confidence: 99%